Legitimising the role of corporate boards and corporate social responsibility on the performance of Malaysian listed companies - Karim, Sitara; Abdul Manab, Norlida; Ismail, Rusmawati (Sage Journal, 2019)
The prime objective of this study is to investigate the legitimate role of corporate boards and corporate social responsibility on the performance of Malaysian listed companies during 2006–2017. Elements of corporate boards include board size, board independence and board diversity, whereas corporate social responsibility (CSR) dimensions constitute marketplace, environment, community and workplace. Both accounting-based (return on assets [ROA], return on equity [ROE]) and market-based (earnings per share [EPS]) performance measures have been employed for measuring performance. Pooled ordinary least squares method (OLS) and multiple regressions are used to estimate the dataset. Findings reveal larger board size and higher board independence positively affect firm performance and significantly legitimise the board role in firms. However, the presence of women on Malaysian corporate boards does not legitimate the performance due to their lower percentage on board, hence insignificantly affecting firm value. Additionally, out of four CSR dimensions, only marketplace is positively and significantly related to EPS and negatively and significantly related to ROA. Conversely, environment, community and workplace are insignificantly related to all performance measures, leaving firms in a questionable legitimate state. This study embraces support from agency theory,resource dependence theory, legitimacy theory and stakeholder theory. However, this research raises questionable insights for regulatory bodies and academicians in the form of corporate legitimacy.